Oxidation and Microstructural Behaviors at 1200 °C of 32.5 wt.% Cr–Containing Co–Based Alloys Strengthened by HfC Carbides - Patrice Berthod (Crystals, 2022)
Two alloys based on cobalt, designed to be reinforced by HfC and containing chromium with content beyond 30 wt.%, were produced by casting. They were subjected to a 46 h–long isothermal exposure at 1200 °C in synthetic air with thermogravimetric monitoring of the oxidation progress. In the as–cast state, the two alloys contain high quantities of script–like shaped HfC carbides. Both of them demonstrated a much better behavior than previous similar alloys containing only 25 wt.% Cr. After 46 h at 1200 °C, the morphology of the carbides had almost not evolved. The control of the creep behavior at 1200 °C showed that these oxidation–resistant alloys are, additionally, as creep–resistant as the 25 wt.% Cr containing previous alloys.